Non-occlusive mesenteric ischaemia in out of hospital cardiac arrest survivors. Issue 5 (1st August 2018) - Wurm, Raphael; Cho, Anna; Arfsten, Henrike; van Tulder, Raphael; Wallmüller, Christian; Steininger, Philipp; Sterz, Fritz; Tendl, Kristina; Balassy, Csilla; Distelmaier, Klaus; Hülsmann, Martin; Heinz, Gottfried; et al.
Abstract: Background and aim of the study: Non-occlusive mesenteric ischaemia (NOMI) is characterised by hypoperfusion of the intestines without evidence of mechanical obstruction, potentially leading to extensive ischaemia and necrosis. Low cardiac output appears to be a major risk factor. Cardiopulmonary resuscitation aims at restoring blood flow after cardiac arrest. However, post restoration of spontaneous circulation, myocardial stunning limits immediate recovery of sufficient cardiac function. Since after successful cardiopulmonary resuscitation patients are often ventilated and sedated, NOMI might be underdiagnosed and potentially life-saving treatment delayed. Material and methods: A prospectively maintained multi-purpose cohort of out of hospital cardiac arrest survivors, who had successful restoration of spontaneous circulation, was used for this retrospective database analysis. Patients' charts were screened for clinical, radiological or pathological evidence of NOMI and clinical data were collected. Results: Between 2000 and 2014, 1780 patients who were successfully resuscitated after out of hospital cardiac arrest were screened for NOMI. Twelve patients (0.68 %) suffered from NOMI and six of those died (50 %). Patients suffering from NOMI tended to have a longer duration until restoration of spontaneous circulation (27 vs . 20 min, p =0.128) and had significantly higher lactate (14 mmol/l vs . 8 mmol/l, p =0.002) and base deficit levels at admission (−17 vs . −10, p =0.012). Median leukocyte counts in NOMI patients peaked at the day of diagnosis. Conclusion: NOMI is a rare but life-threatening and potentially curable complication following successful cardiopulmonary resuscitation. Lactate and base deficit at admission could help to identify patients at risk for developing NOMI who might benefit from increased clinical attention.